Feeding behavior and diet preferences of Sumatran orangutans (Pongo abelii Lesson 1827) at Soraya Research Station, Mount Leuser National Park, Indonesia - IQBAR IQBAR; ROSY SAFRIANA; FAUZIAH FAUZIAH (Society for Indonesian Biodiversity, 2024)
Abstract. Iqbar I, Safriana R, Fauziah F. 2024. Feeding behavior and diet preferences of Sumatran orangutans (Pongo abelii Lesson 1827) at Soraya Research Station, Mount Leuser National Park, Indonesia. Biodiversitas 25: 1788-1796. The Sumatran orangutan (Pongo abelii Lesson 1827) is an exclusive and indigenous primate species inhabiting the forests of Sumatra. Unfortunately, the species is constantly threatened by habitat loss and depletion of food sources due to human activities such as deforestation for agriculture and plantations. This study was conducted at the Soraya Research Station in the Leuser Ecosystem (Mount Leuser National Park), Indonesia, from December 2021 to July 2022 to investigate the Sumatran orangutan's feeding behavior and diet preferences. Focal Animal Sampling was employed as the observation method, with data collected every 2 minutes. The parameters measured were eating behavior, body position during feeding, and type of food consumed. The sample included three orangutans: one adult male, one adult female, and one juvenile male. Behavioral observations were carried out for 18,000 minutes, namely 2,160 minutes for adult males, 7,920 minutes for adult females and 9,720 minutes for juvenile males. The study found that the total eating behavior was 6204 minutes, with chewing being the most frequent behavior observed. Orangutans were more likely to eat while hanging. The diet included 41 species from 20 families, and the orangutan's preferred food was cambium damli (Streblus elongatus) from the Moraceae family. This research describes the types of food eaten by orangutans and is expected to provide information for research station managers to ensure the availability of these plants.